Acrylonitrile‐Linked Covalent Organic Frameworks Enable Fast Stimulus‐Responsive Fluorescence with High Quantum Yield via Fluorine Chemistry. Issue 8 (30th March 2022) - Yang, Meijia; Fang, Long; Li, Jing; Yuan, Zhongke; Yu, Dingshan; Chen, Xudong
Abstract : Covalent organic frameworks (COFs) have emerged as potential light‐emitting polymers for optoelectronic and optical devices, but their smart responsiveness to environmental stimuli has seldom been explored particularly for alkene‐linked conjugated COFs, which limits their application scope in "smart" systems. Herein, fluorine chemistry coupled with acrylonitrile linkage is introduced as a "one‐stone‐three‐bird" strategy to produce a smart COF with rapid pH‐responsive absorption and fluorescence, high fluorescence quantum yield (QY), and good crystallinity. In addition to increased crystallinity, the newly designed fluorinated acrylonitrile‐linked COF (TF‐COF) produces 20% enhancement in fluorescence QY and more rapid responsiveness of absorption and fluorescence under acid–base induction compared to the nonfluorinated counterpart. Impressively, the yielded QY reaches 33.6% in solid states and 41.0% in tetrahydrofuran dispersion, surpassing most existing COF materials. The synergy effect of fluorine chemistry induced charge redistribution and acrylonitrile linkage enabled reversible C═C bonds contributes to the rapid responsiveness, high fluorescence QY, and good crystallinity. The developed TF‐COF can be utilized as a responsive phosphor to endow image encryption with high coloration and good reversibility, and as an encryption data carrier via simple handwriting. Abstract : Fluorine chemistry not only enables acrylonitrile‐linked covalent organic frameworks intense fluorescence with quantum yield (QY) of 33.6% in solid states and 41.0% in tetrahydrofuran dispersion—superior to almost all reported covalent organic frameworks (COFs) along with improved crystallinity, but also affords rapid responsive absorption and fluorescence under acid/base status, which can be used in information encryption.